HIV-Positive Status Disclosure and Associated Factors among Children in North Gondar, Northwest Ethiopia. (13th December 2012) - Negese, Digsu; Addis, Kefyalew; Awoke, Akilew; Birhanu, Zelalem; Muluye, Dagnachew; Yifru, Sisay; Megabiaw, Berihun
Abstract : Introduction . Clinical reports have indicated positive outcomes associated with disclosure of HIV-positive status in children. This study assessed the level and associated factors of HIV-positive status disclosure to HIV-infected children in northwest Ethiopia. Methods . Institution-based cross-sectional study was conducted among HIV-positive children from March to April 2012. Data were collected using a structured questionnaire by face-to-face interview technique. Bivariate and multivariate analyses were performed. Results . Of the 428 children, 169 (39.5%) were disclosed their HIV-positive status. The mean age of HIV-positive status disclosure was at 10.7 (±2.3) years. Having a nonbiological parent (AOR = 4.14, 95% CI: 1.22, 14.04), child's age older than 10 years (AOR = 8.54, 95% CI: 4.5, 15.53), and death of a family member (AOR = 2.04, 95% CI: 1.16, 3.6) were significantly and independently associated with disclosure of HIV-positive status to infected children. Conclusions . The rate of disclosure of HIV-positive status to infected children still remains low in North Gondar. Hence, it is important to target children living with their biological parents and having young parents and children younger than 10 years. The guideline for disclosure of children with HIV/AIDS should be established in an Ethiopian context.